دلالات الأدوات العاطفة للربط النصي عند الزمخشري وأبي حيان من أول فاتحة الكتاب الى نهاية سورة الأنعام: The semantics Links by conjunctions in the selected Quranic chapters as discussed by Al-Zamakhshari and Abu Hayyan) From the first chapter “al-Fa:tiha” to the end of Surah “al-Ana:m” - Farah Naz; Dr. Hafiz Muhammad Bashir (MEI, 2023)
All praise be to the Lord of the Worldsand peace and blessingsbe on the Prophet Muhammad,his family and his Companions. Amongst the scholarly discussions in the area of Arabic Syntax is the discussion of relations that connect the words with each other in a structure. The semantics Links by conjunctions in the selected Quranic chapters as discussed by Al-Zamakhshari and Abu Hayyan and my research will deal with the semantics Links by conjunctions a topic that has been attracting the attention of the grammarians and these are: link by the letter ( waw) link by the letter(Fa) link by the letter (Summa) link by the letter ( Hatta) link by the letter ( Awo) link by the letter (Am) Link by the letter (bal) The researcher refers to primary and secondary sources pertinent to the subject matter which includes classical records and contemporary books. All the relevant sources are given at the footnotes of the article.